Analysis of the dependence of the level demand for services from the service centers pay consumers - Мастепан, Микола Антонович; Мінаков, Дмитро Михайлович; Волобуєва, Тетяна В’ячеславівна; Каверин, Олексій Сергійович (Eastern-European Journal of Enterprise Technologies, 2012)
The approach to solving complex problem was designed: the formation of prices (pricing) for the car service, the forecasting and planning of technical and technological development of production. The logistic model for the definition of key indicators of efficiency functioning and forecasting production of services was represented